A treadmill running research protocol to assess dynamic visual acuity and balance for athletes with and without recent concussion history - Mitchell, K. M.; Dalton, K. N.; Cinelli, M. E. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Athletes interpret dynamic visual scenes quickly and accurately during physical exertion. It is important to understand how increased exertion may impact vision and cognition following sport-related concussion (SRC).